$\displaystyle f(x)\equiv f(x)-f(a) \equiv c_1(x-a)+...+c_n(x^n-a^n)$

$\displaystyle \equiv (x-a)(c_1+c_2(x+a)+...+c_n(x^{n-1}+x^{n-2}a+...+xa^{n-2}+a^{n-1})) $

$\displaystyle \equiv (x-a)g(x)$

where $\displaystyle g(x)$ is of degree $\displaystyle \leq n-1$. Now use the fact that $\displaystyle p$ is prime to show that any other roots of $\displaystyle f(x)$ must in fact be roots of $\displaystyle g(x)$, and apply the induction hypothesis to obtain the desired factorization for $\displaystyle f(x)$.

Hope that helps!